Growth, inequality and poverty dynamics in Mexico - Alberto Javier Iniguez-Montiel; Takashi Kurosaki (Latin American Economic Review, 2018)
In this study, we examine the contributions of growth and redistribution to poverty reduction in Mexico during the period from 1992 to 2014, using repeated cross-section household data. We first decompose the observed changes in poverty reduction into components arising from growth, improved income distribution, and heterogeneous inflation. We find the component of inflation to be non-negligible and highly detrimental to the poor, as the inflation experienced by them has been higher than the national average since 2008. The decomposition also shows improvement in income distribution to be the main contributor to poverty reduction in Mexico. In the second part of our analysis, we compile a unique panel dataset at the state level from the household data and estimate a system of equations that characterize the dynamic relationship between growth, inequality, and poverty, being careful to avoid spurious correlation arising from data construction. The GMM regression results show that Mexican states are characterized by income and inequality convergence, that lower levels of inequality tend to spur growth in the economy, that increasing income/consumption levels contribute to reducing inequality, and that poverty reduction is highly determined by inequality levels in the previous period. This implies that once a small perturbation occurs in a state that improves the distribution of income, the state is expected to experience sustained income growth and accelerated poverty reduction simultaneously in subsequent periods.
Keywords: C23; I32; O15; O47; O54; 330; Dynamics; GMM estimation; Growth; Inequality; Poverty; Mexico